The influence path of community green exposure index on activity behavior under multi-dimensional spatial perception - Zheng, Lingyu; Zhao, Yixue; Duan, Ran; Yang, Wanting; Wang, Zhigang; Su, Jiafu (Frontiers in Public Health, 2023)
The purpose of this research is to reveal the internal relationship between community green space, space perception and activity behavior response to supplement the lack of research results on the binary relationship between green space and behavior. Nine residential community green space and 398 residents were selected as the research objects. Thematic clustering and factor identification were used to determine the spatial perception dimensions of community green space that residents concerned. The analysis of green exposure index, spatial perception evaluation and activity behavior survey were combined to determine the influence of green exposure index on spatial perception and activity behavior and its internal correlation path. According to research data, community GVI and NDVI negatively affected the perception factor, while the perception factor positively affected the activity frequency. The SEM model shows that green exposure index stimulated activity behavior through the intermediate effect of the internal perception path of perceived landscape quality-perceived workability-perceived accessibility. Spatial perception as the basis of the instantaneous emotional reaction process may affect people’s choices for activities but unable to extend the activities duration. The internal association among community green space, spatial perception and physical activity behavior develops on the basis of spatial patterns of certain scales. This study provides a theoretical basis for understanding the spatial experience and residents’ behavior needs, evaluating the quality of urban green space scientifically, and promoting the optimization of community green space structure.